The shearing performance of a beam-column joint in a reinforced concrete frame subjected to bidirectional loading. Issue 15 (November 2019) - Li, Zhenbao; Cui, Yanwei; Song, Kun; Ma, Hua; Tang, Zhenyun
The anti-seismic capability of beam-column joints in reinforced concrete frame structures undergoing bidirectional loading may be lower than the designed capability for unidirectional earthquake action. To date, detailed calculation methods for the shear capability and shearing performance for joints in reinforced concrete frames subjected to bidirectional loading have not been reported. In this work, the shear mechanism of the beam-column joint in a reinforced concrete frame under bidirectional loading is analyzed. The study shows that when a synthetic shear force is imposed on the joint, the oblique compression zone comes into being at the corner of the joint, and the oblique compression strut is formed in the core area of the joint, which is different from the shear mechanism of the joint under unidirectional loading. A shear capacity calculation model is established based on the strut-and-tie model. Through the testing of reinforced concrete frame joints under bidirectional monotonous loading, the combined shear and deformation in the joint are obtained, the mechanical properties in each principal plane and in the combined shear action plane are analyzed, the shearing performance of the joints in a reinforced concrete frame under bidirectional loading is defined, and the shear contributions of hoop and column reinforcement are verified. The predicted values of the shear capability in this work are in good agreement with the reported experimental results.